2015
DOI: 10.1007/s11307-015-0889-6
|View full text |Cite
|
Sign up to set email alerts
|

Establishing On-Site Reference Values for 123I-FP-CIT SPECT (DaTSCAN®) Using a Cohort of Individuals with Non-Degenerative Conditions

Abstract: We here propose a convenient approach to calculate site-specific reference limits for DaTSCAN® outcomes not requiring scanning healthy controls. The method appears to yield robust values that range within nearly identical limits as those obtained in healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 47 publications
9
29
0
Order By: Relevance
“…First, applying semi-quantitative assessment yielded only two subjects with normal values. This supports our early hypothesis that routine visual assessment alone may not be reliable enough to define scan normality, at least in some cases with borderline uptakes, as already shown in a previous study [22]. Second, a detailed review of the visual stage by two experts showed that only one of these 10 patients could be considered as having a definite normal (stage 0) visual assessment.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…First, applying semi-quantitative assessment yielded only two subjects with normal values. This supports our early hypothesis that routine visual assessment alone may not be reliable enough to define scan normality, at least in some cases with borderline uptakes, as already shown in a previous study [22]. Second, a detailed review of the visual stage by two experts showed that only one of these 10 patients could be considered as having a definite normal (stage 0) visual assessment.…”
Section: Discussionsupporting
confidence: 88%
“…Establishment of local reference values has been reported previously using a large cohort of patients with non-degenerative conditions and a normal 123 I-ioflupane SPECT scan [22]. Importantly, it has been demonstrated that data obtained from this population were nearly identical with those from healthy subjects, thus validating the method.…”
Section: Determination Of Local Semi-quantitative Reference Valuesmentioning
confidence: 56%
See 1 more Smart Citation
“…Fahmi et al European Journal of Hybrid Imaging (2020) 4:5 volumes of interest, as was previously reported by others (e.g., (Nicastro et al 2016;Varrone et al 2013)). We obtained an overall rate of SBR decline per decade, averaged over all striatal VOIs and over both genders, of 4.80% (Flash3D) and 5.02% (FBP).…”
Section: Discussionsupporting
confidence: 69%
“…As control group (CG), a series of patients with clinical diagnosis of Essential Tremor (ET) 34, 35 (all with a normal 123 I-FP-CIT imaging), were considered. Written informed consent from the subject was obtained for each procedure.…”
Section: Methodsmentioning
confidence: 99%